2013
DOI: 10.1016/s0254-6272(13)60161-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adverse events reported in Traditional Iranian Medicine following administration of aqueous extract of Herba Portulacae Oleraceae seed

Abstract: Because of the short duration of action of adenosine, catecholamines and niacin seems to be the major role in appearance of adverse events reported in TIM for Herba Portulacae Oleraceae seed. Mechanisms with consideration of receptor types and pharmacokinetics of catecholamine and niacin are warranted to confirm this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The mean score of breast fissures significantly decreased and no complications were observed after the patients were treated with Portulaca oleracea L. cream (2%). It is worth noting that adverse events such as itching and tingling of whole body, dyspnea and tachycardia were reported after the systemic administration of Portulaca oleracea seed extract ( Mirabzadeh et al, 2013 ).…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…The mean score of breast fissures significantly decreased and no complications were observed after the patients were treated with Portulaca oleracea L. cream (2%). It is worth noting that adverse events such as itching and tingling of whole body, dyspnea and tachycardia were reported after the systemic administration of Portulaca oleracea seed extract ( Mirabzadeh et al, 2013 ).…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…The seed of P. oleracea, commonly known as purslane is considered as an ancient drug which has been used for the treatment of several diseases such as gastrointestinal ulceration, urinary tract infections, kidney stone and menstruation disorders in traditional and folklore medicine of different countries (Mirabzadeh et al, 2013). It has been suggested that the seeds possess a pronounced antidiabetic activity in recipes of traditional medicines.…”
Section: Portulaca Oleracea (Portulacaceae)mentioning
confidence: 99%
“…ese properties utterly provide considerable benefits to prevent the heart attacks and strengthening the immune system. Besides, they have favorable effects on cholesterol and triglyceride levels [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%